Small noncoding RNAs and sperm nuclear basic proteins reflect the environmental impact on germ cells - Ferrero, Giulio; Festa, Rosaria; Follia, Laura; Lettieri, Gennaro; Tarallo, Sonia; Notari, Tiziana; Giarra, Antonella; Marinaro, Carmela; Pardini, Barbara; Marano, Alessandra; Piaggeschi, Giulia; Di Battista, Carla; et al. (Molecular medicine (Cambridge, Mass.), 2024)
Background Molecular techniques can complement conventional spermiogram analyses to provide new information on the fertilizing potential of spermatozoa and to identify early alterations due to environmental pollution. Methods Here, we present a multilevel molecular profiling by small RNA sequencing and sperm nuclear basic protein analysis of male germ cells from 33 healthy young subjects residing in low and high-polluted areas. Results Although sperm motility and sperm concentration were comparable between samples from the two sites, those from the high-pollution area had a higher concentration of immature/immune cells, a lower protamine/histone ratio, a reduced ability of sperm nuclear basic proteins to protect DNA from oxidative damage, and an altered copper/zinc ratio in sperm. Sperm levels of 32 microRNAs involved in intraflagellar transport, oxidative stress response, and spermatogenesis were different between the two areas. In parallel, a decrease of Piwi-interacting RNA levels was observed in samples from the high-polluted area. Conclusions This comprehensive analysis provides new insights into pollution-driven epigenetic alterations in sperm not detectable by spermiogram. Graphical Abstract